2002
DOI: 10.1002/cyto.10160
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of cells to static magnetic field accelerates loss of integrity of plasma membrane during apoptosis

Abstract: Much attention is being paid to the biologic effects of magnetic fields (MFs). Although MFs enhance tumorigenesis, they are neither mutagenic nor tumorigenic. The mechanism of their tumorigenic effect has not been elucidated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 34 publications
2
43
0
2
Order By: Relevance
“…At this regard, our undergoing studies demonstrated that the magnetic exposure of human peripheral blood in vitro, altered the cholesterol level of the plasma. Furthermore the deep pits observed at the highest SMF intensity might account for the decreased membrane integrity and increased permeability to impermeant dyes we have observed in a previous study (11).…”
Section: Discussionsupporting
confidence: 54%
“…At this regard, our undergoing studies demonstrated that the magnetic exposure of human peripheral blood in vitro, altered the cholesterol level of the plasma. Furthermore the deep pits observed at the highest SMF intensity might account for the decreased membrane integrity and increased permeability to impermeant dyes we have observed in a previous study (11).…”
Section: Discussionsupporting
confidence: 54%
“…According to product manuals, these membrane-permeable and nontoxic inhibitors enter the cell and bind covalently to the reactive cysteine residue that resides on the large subunit of the active caspase heterodimer. This system undoubtedly represents a useful research tool to monitor apoptosis progression (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). It was also used to study the intracellular localization of caspases and their changes during the apoptosis (15).…”
mentioning
confidence: 99%
“…Comparative studies with FCM and LSC have shown that data obtained by both technologies are consistent with each other for the study of apoptosis or necrosis (30). LSC is a reliable tool for the intracellular staining of p53 protein (31) and DNA ploidy analysis (32).…”
Section: Discussionmentioning
confidence: 58%